Synthesis and characterization of Cu, Ni and Zn tungstates for mulfunctional applications: catalysis, photocatalysis and pigment - Lima, Naiara Arantes (2021)
In this research, copper (CuWO4), nickel (NiWO4) and zinc (ZnWO4) tugstates were applied in three different themes: catalysis, photocatalysis and pigments. In the catalysis application, Cu, Ni and Zn tungstates were synthesized by the polymeric precursor method (PPM, and their catalytic activity was evaluated as a function of the conversion of thioanisole to methyl phenyl sulfoxide and methyl phenyl sulfone, according to the catalyst nature, reaction time, temperature and H2O2 concentration. CuWO4 was the most effective catalyst mainly due to the greater number of vacancies/oxygen mobility proportional to the increased catalytic activity. In the photocatalysis application, copper tunsgtate was synthesized by the coprecipitation (CM), microwave-assisted hydrothermal (HM) and polymeric precursor (PPM) methods, and its photocatalytic activity was evaluated for the degradation of the Rhodamine B dye. The study was carried out in order to understand the influence of the synthesis method on the material properties, and consequently on the photocatalytic response. The influence of the oxidizing agent H2O2 and the sodium oxalate and silver nitrate scavengers were evaluated in the reaction. With the addition of Ag+ ions, the recombination rate was minimized and the reaction occurred more efficiently for CuWO4 (PPM) (20 min = 100% of degradation). The most relevant properties that may have influenced catalytic efficiency were surface charge (-38.5 for PPM < -29.7 for CM < -16.2 for HM) and the number of oxygen vacancies (PPM > HM > CM). In the pigment application, NiWO4 was synthesized by the polymeric precursor method for the manufacture of a yellow pigment. The material was evaluated for its stability, color pattern, luminescence and reproducibility. The results showed that NiWO4, whose yellow color was due to the electronic transitions of Ni2+, proved to be stable for calcination temperatures above 700 °C. Additionally, when illuminated this material presented light emission in the blue-green region, indicating luminescent properties.